Assessment of fodder conservation in smallholder dairy farming systems in highland and midlands of eastern Kenya - Kogo, Thomas Kipchoge (UoEm, 2025)
GENERAL ABSTRACT The dairy industry is important for its contribution to the living standard of people, industries, foreign exchange and 4% of the total GDP in Kenya. Productivity of 7.8 liters/cow/day is low and attributed to poor feeding and contribution to high emission of greenhouse gases (GHGs). Fodder scarcity poses a challenge to the achievement of high productivity, while mitigation of fodder scarcity through fodder conservation remains low. Despite common challenges, farms perform differently, in different farm locations with some farms, also called positive deviants (PDs) conserving adequate fodder. In the highlands and midlands of eastern Kenya, information on fodder conservation among smallholder dairy farming systems is limited. The adoption levels and the intensity of fodder conservation technologies including silage and hay, factors affecting the adoption and use of such technologies in (peri-) urban locations and strategies used by PDs in fodder conservation are unknown. Therefore, the study sought to assess fodder conservation technologies among smallholder dairy farming systems in the highlands and midlands of Tharaka-Nithi County, Kenya. Specifically: to determine factors affecting the adoption intensity of fodder conservation. To determine factors of fodder conservation technologies adoption in urban and peri-urban areas. To determine strategies that distinguish PDs from peers (non-PDs) in fodder conservation. A cross-sectional survey was conducted on smallholder dairy farms producing and conserving fodder in Tharaka Nithi County. Multistage sampling procedures were used: purposive sampling of the Sub- counties and locations, random selection of villages and proportional selection of 242 farms through snowball chain referral. The questionnaire was used to collect information, which included: household socio-demographics, husbandry practices, farm characteristics and fodder conservation characteristics. Two towns were chosen purposively to represent urban locations i.e. Chuka (UL, n=68) and peri-urban locations Chogoria (PUL, n=93) in Chuka and Maara Sub-Counties respectively (Total n=161), due to the relatively high number of urban dwellers. Additionally, the PDs (n=24) conserved fodder adequate to last the dry season and had a milk yield of ≥15 kg/cow/day. While non-PDs (n=97) do not qualify for both criterion as farms qualifying for one criteria were discarded. Multiple regression analysis was applied to explain the quantity of fodder conserved. The Multivariate Regression (MVR) model was used to identify and estimate simultaneously the determinants of fodder conservation technologies adoption. Logit regression was used to examine variables that influence the probability of PDs. The study found that most farms were headed by older males who had basic education. Fodder was scarce during the dry season in most farms. Fodder conserved included; silage was conserved in the least number of farms only 26%, but the highest in the quantity of fodder conserved (13 tons); hay was conserved in 40% of the farms, but the quantity conserved was the least (2 tons); crop residue storage was the major conserved fodder by 85% of the farms and the quantity conserved was 5 tons. Quantities of fodder conserved were affected by land size, herd size, duration planned to use conserved fodder, main fodder source during scarcity and the fodder conservation technologies used (silage and hay). Quantities of silage and hay conserved were higher in urban location (UL) than in peri- urban locations (PUL) farms. Crop residue storage was conserved more in non-PD farms, especially in PUL farms. Fodder conserved in UL and PUL was influenced by farm location, land size, herd size, total milk yield per farm, sex, source of fodder during feed scarcity, extension services, period the current stock is expected to last, use of concentrate feeds and breed kept. Access to extension services, milk yield, land size, land under xivfodder, period to use conserved fodder, total herd size, and different combinations of fodder conservation technologies differ between PDs and non-PDs. PDs in fodder conservation are favored by a high level of education, access to extension services, large land, herd size and high milk yield. The study shows knowledge production resources and technology used as important in fodder conservation. Recommended mitigation measures target more education on fodder conservation technologies as well as increasing the adoption of improved fodder production. Knowledge advancement of farmers and policymakers through education and extension increases milk production. Therefore, policymakers can focus on creating enabling policies that promote the adoption of improved technologies as used by PDs to support fodder production and conservation to improve productivity and inform the direction of future research.
Thesis Abstract
Keywords: Fodder Conservation; Dairy Farming Systems; Pastures